Negative electrode active material, negative electrode slurry, negative electrode plate, preparation method of negative electrode plate and lithium ion battery

Through the combination of graphite, silicon oxide and MnPS3, combined with the use of PAA-CMC binder, the capacity decay caused by volume changes in the lithium-ion battery negative electrode material during lithiation is solved, and high specific capacity and excellent rate performance.

CN119153652APending Publication Date: 2024-12-17SHENZHEN BAK POWER BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411286722.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The volume changes greatly during the lithiation process of lithium-ion battery anode materials, resulting in poor capacity decay and circulation performance, especially the expansion problem of silicon-based anode materials is difficult to solve.

Method used

Using a combination of graphite, silicon oxide compound and metal phosphorus trichalcogenide MnPS3, a negative electrode active material is prepared by mixing the negative electrode slurry and preparing the negative electrode sheet. The unique structure of MnPS3 and the interface interaction between the PAA-CMC binder is used to form a stable The electrode structure is used to buffer volume changes.

Benefits of technology

The high specific capacity and excellent rate charging performance of lithium-ion batteries are achieved, and the electrode aggregation and crushing caused by volume changes are reduced, and the circulation performance and the mechanical strength of the electrode are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153652A_ABST
    Figure CN119153652A_ABST
Patent Text Reader

Abstract

The invention provides a negative active material, negative slurry, a negative plate, a preparation method of the negative plate and a lithium ion battery, and relates to the technical field of lithium ion battery preparation. The negative electrode active material comprises graphite, a silicon-oxygen compound and MnPS3; the mass of the silicon-oxygen compound accounts for 12-17% of the total mass of the negative electrode active material; and the mass of the MnPS3 accounts for 3-8% of the total mass of the negative electrode active material. MnPS3 (manganese phosphorus trisulfide) has a unique layered Van der Waals structure, so that alkali metal ions can be quickly deintercalated, when lithium ions are stored, a single-phase phosphorus out-phase structure is irreversibly broken along with a P-S bond after a first charge-discharge cycle is finished, and a mixed phase formed in situ can be used as an inert buffer matrix of each other, so that the lithium ion storage capacity is improved. Therefore, the aggregation and crushing of the electrode caused by volume change are buffered, and the MnPS3 negative electrode shows ideal specific capacity and excellent rate charging property due to good electron and ion conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium ion battery preparation, and in particular to a negative electrode active material, a negative electrode slurry, a negative electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art

[0002] With the development of market demand, lithium-ion batteries are required to have the characteristics of high energy density, excellent rate performance, and good cycle performance. The main negative electrode materials in the current lithium-ion battery market are graphite and silicon-based negative electrodes, but these two materials have their own advantages and disadvantages in the performance of lithium batteries. Traditional graphite negative electrode materials have a small volume change rate and stable structure during the lithiation process, but their theoretical specific capacity is 372mAh / g. The low specific capacity limits the improvement of the energy density of lithium-ion batteries; the theoretical capacity of silicon-based negative electrodes is as high as 4200mAh / g, which is the lithium-ion battery negative electrode material with the highest known specific capacity, but it produces a serious volume effect during lithiation, and the volume of silicon will expand by more than 300%. The huge volume change will bring a series of problems, and as the silicon content increases, the first coulomb efficiency will become lower and lower.

[0003] Therefore, how to improve the capacity of lithium batteries and improve the capacity decay caused by electrode expansion is an urgent problem that needs to be solved. Summary of the invention

[0004] The purpose of the present application is to provide a negative electrode active material, a negative electrode slurry, a negative electrode sheet and a preparation method thereof and a lithium ion battery to solve the above problems.

[0005] To achieve the above objectives, the present application provides a negative electrode active material in the first aspect, including graphite, silicon oxide and MnPS 3 ;

[0006] The mass of the silicon oxide compound accounts for 12%-17% of the total mass of the negative electrode active material;

[0007] The MnPS 3 The mass of the negative electrode active material accounts for 3%-8% of the total mass of the negative electrode active material.

[0008] The second aspect of the present application provides a negative electrode slurry, wherein the raw materials thereof, calculated on a total mass basis, include 48%-52% of the negative electrode active material, 10%-15% of a conductive agent, 2%-6% of a binder and 30%-35% of a solvent.

[0009] Optionally, the negative electrode slurry satisfies at least one of the following conditions:

[0010] A. The conductive agent includes one or more of conductive graphite, carbon nanotubes, and graphene;

[0011] B. The solvent includes water.

[0012] Optionally, the binder includes sodium polyacrylate (PAA) and / or sodium carboxymethyl cellulose (CMC).

[0013] The third aspect of the present application provides a negative electrode sheet, the raw material of which includes the negative electrode slurry.

[0014] The fourth aspect of the present application provides a method for preparing the negative electrode sheet, comprising:

[0015] slurry-adjusting the negative electrode slurry to obtain slurry-adjusted slurry;

[0016] The slurry after slurry adjustment is coated on a current collector to obtain the negative electrode sheet.

[0017] Optionally, the viscosity of the slurry after slurry adjustment is 1900mPa.s-2200mPa.s.

[0018] Optionally, the surface density of the negative electrode sheet is 15 mg / cm 2 -18mg / cm 2 .

[0019] A fifth aspect of the present application provides a lithium-ion battery, comprising the negative electrode sheet or the negative electrode sheet prepared by the negative electrode sheet preparation method, a positive electrode sheet and a separator.

[0020] Optionally, the lithium-ion battery meets at least one of the following conditions:

[0021] A. The active material in the positive electrode sheet includes high nickel NCM, the chemical formula of which is LiNi x Co y Mn z O 2 , 0.8≤x≤0.98, y≤0.2, z≤0.2, x+y+z=1;

[0022] B. The surface density of the positive electrode is 45 mg / cm 2 -48mg / cm 2 ;

[0023] C. The lithium-ion battery includes a 21700 lithium-ion battery;

[0024] D. The diaphragm includes one or more of a PP diaphragm, a PE diaphragm, and a ceramic-coated diaphragm.

[0025] Compared with the prior art, the beneficial effects of this application include:

[0026] The negative electrode active material provided by the present application, metal phosphorus trisulfide MnPS 3(Manganese phosphorus trisulfide) has excellent mechanical properties and lithium storage performance. Its unique layered van der Waals structure is conducive to the rapid deintercalation of alkali metal ions. When storing lithium ions, the single-phase phosphorus heterogeneous structure is accompanied by irreversible breakage of PS bonds after the first charge and discharge cycle. The mixed phase formed in situ can be used as an inert buffer matrix for each other, thereby buffering the aggregation and crushing of the electrode caused by volume change. Due to its good electronic and ionic conductivity, MnPS 3 The negative electrode shows an ideal specific capacity and excellent rate charging performance; graphite, silicon oxide and MnPS 3 The combination of graphite materials has high conductivity and good chemical stability, silicon oxide materials have high specific capacity advantages, and a certain amount of MnPS doped 3 It is beneficial to alleviate the expansion of silicon oxygen during the electrochemical reaction; 12%-17% silicon oxygen content is a more ideal parameter. Silicon oxygen content exceeding 17% is prone to high temperature effect during the manufacturing process, causing the pole piece structure to collapse.

[0027] The negative electrode slurry provided by the present application forms an interface interaction between the binder and the negative electrode active material, has good dispersibility, viscoelasticity and stability, and is conducive to subsequent coating uniformity.

[0028] The negative electrode sheet provided in this application has excellent performance, no process problems such as material falling, bubbles, creases, etc., and has low internal resistance.

[0029] The method for preparing the negative electrode sheet provided in the present application is simple to prepare.

[0030] The lithium-ion battery provided in the present application has a high capacity and good rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0032] Figure 1 The 0.5C charging and 0.2C discharging capacity-voltage curves of the lithium-ion batteries prepared in Examples 1-3;

[0033] Figure 2 The 0.5C charging and 1C discharging capacity-voltage curves of the lithium-ion batteries prepared in Examples 1-3;

[0034] Figure 3 The capacity retention rate diagram of the lithium ion batteries prepared in Examples 1-3 at 0.5C, 1C, 2C, 3C, 4C, 5C, and 6C charging rates compared with 0.2C charging rate;

[0035] Figure 4 This is a graph showing the 25°C cycle capacity retention rate of the lithium-ion batteries prepared in Examples 1-3. DETAILED DESCRIPTION

[0036] As used herein:

[0037] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0038] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0039] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0040] In these examples, parts and percentages are by mass unless otherwise indicated.

[0041] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0042] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0043] The present application provides a negative electrode active material, including graphite, silicon oxide and MnPS 3 ;

[0044] The mass of the silicon oxide compound accounts for 12%-17% of the total mass of the negative electrode active material;

[0045] Optionally, the mass of the silicon oxide compound accounts for 12%, 13%, 14%, 15%, 16%, 17% or any value between 12% and 17% of the total mass of the negative electrode active material;

[0046] The MnPS 3 The mass of the negative electrode active material accounts for 3%-8% of the total mass of the negative electrode active material.

[0047] Optional, MnPS 3 The mass of the negative electrode active material accounts for 3%, 4%, 5%, 6%, 7%, 8% or any value between 3% and 8% of the total mass of the negative electrode active material.

[0048] A second aspect of the present application provides a negative electrode binder, comprising PAA-CMC, which accounts for 2%-6% of the negative electrode slurry based on 100% total mass of the negative electrode slurry.

[0049] The second aspect of the present application provides a negative electrode slurry, wherein the raw materials thereof, calculated on a total mass basis, include 48%-52% of the negative electrode active material, 10%-15% of a conductive agent, 2%-6% of a binder and 30%-35% of a solvent.

[0050] Optionally, based on the total mass of the raw materials of the negative electrode slurry being 100%, the negative electrode active material may be 48%, 49%, 50%, 51%, 52% or any value between 48% and 52%, the conductive agent may be 10%, 11%, 12%, 13%, 14%, 15% or any value between 10% and 15%, the binder may be 2%, 3%, 4%, 5%, 6% or any value between 2% and 6%, and the solvent may be 30%, 31%, 32%, 33%, 34%, 35% or any value between 30% and 35%.

[0051] In some embodiments, the negative electrode slurry satisfies at least one of the following conditions:

[0052] A. The conductive agent includes one or more of conductive graphite, carbon nanotubes, and graphene;

[0053] In some embodiments the conductive graphite includes acetylene black;

[0054] B. The solvent includes water.

[0055] In some embodiments, the binder includes sodium polyacrylate (PAA) and / or sodium carboxymethylcellulose (CMC).

[0056] In some embodiments, the binder is PAA.

[0057] It should be noted that PAA, as a binder, forms a stable covalent bond through the condensation reaction of its free carboxylic acid with the hydroxyl groups on the surface of silicon particles. This process effectively inhibits the migration of silicon nanoparticles during the charge and discharge cycle and prevents the damage of the electrode structure caused by volume change. PAA not only improves the mechanical strength of the electrode, but also further consolidates the electrode structure. The acid groups on the PAA molecules may react with MnPS 3 Coupling and sustained activation of MnPS 3 , thereby reducing the reduction potential barrier and achieving high utilization of active materials.

[0058] In some embodiments, the binder is PAA and CMC.

[0059] It should be noted that PAA-CMC forms a three-dimensional cross-linked network through esterification reaction, increases stress nodes, has high mechanical strength and good electrochemical coupling effect, and enhances the electrode conductivity effect; PAA-CMC contains abundant carboxyl and hydroxyl groups, which may react with MnPS 3 Coupling and sustained activation of MnPS 3 , thereby reducing the reduction potential barrier and achieving high utilization of active materials. 3 The phosphorus in the MnPS generates strong interfacial interactions and is evenly distributed in the 3 The surface of the battery isolates the active materials from direct contact with the electrolyte, helps to form a thin solid electrolyte interface layer (SEI), and reduces the irreversible loss of active materials.

[0060] The third aspect of the present application provides a negative electrode sheet, the raw material of which includes the negative electrode slurry.

[0061] The fourth aspect of the present application provides a method for preparing the negative electrode sheet, comprising:

[0062] slurry-adjusting the negative electrode slurry to obtain slurry-adjusted slurry;

[0063] The slurry after slurry adjustment is coated on a current collector to obtain the negative electrode sheet.

[0064] In some embodiments, the viscosity of the slurry after slurry adjustment is 1900mPa.s-2200mPa.s.

[0065] Optionally, the viscosity of the slurry after slurry adjustment can be 1900mPa.s, 2000mPa.s, 2100mPa.s, 2200mPa.s or any value between 1900mPa.s and 2200mPa.s.

[0066] It should be noted that the slurry after stirring needs to have good fluidity, stability and uniformity. Slurry states with different fluidities may have slurry viscosity that is too low or too high, sedimentation, agglomeration, uneven dispersion, etc., which will have a great impact on subsequent coating and other processes, causing defects in the macroscopic appearance of the electrode and inconsistency in the microscopic composition of the electrode. When the viscosity of the slurry after adjustment is 1900mPa.s-2200mPa.s, the rubber has better fluidity and uniform particle dispersion, which is conducive to coating uniformity. The resulting lithium battery has higher consistency and better electrical properties.

[0067] In some embodiments, the surface density of the negative electrode sheet is 15 mg / cm 2 -18mg / cm 2 .

[0068] Optionally, the surface density of the negative electrode sheet can be 15 mg / cm 2 、16mg / cm 2 、17mg / cm 2 、18mg / cm 2 or 15mg / cm 2 -18mg / cm 2 Any value in between.

[0069] It should be noted that if the coating surface density is too small, the battery capacity may not reach the nominal capacity. As the surface density increases, the internal resistance of the battery increases. During the charge and discharge cycle, the internal resistance of the battery also increases significantly. At the same time, the reaction rate and migration rate of lithium ions in the electrochemical reaction process decrease, and polarization increases, which is not conducive to fast charging of the battery and affects its cycle performance. 2 -18mg / cm 2 It performs excellently in lithium-ion batteries, with no process problems such as falling off and creases, and has low internal resistance.

[0070] A fifth aspect of the present application provides a lithium-ion battery, comprising the negative electrode sheet or the negative electrode sheet prepared by the negative electrode sheet preparation method, a positive electrode sheet and a separator.

[0071] In some embodiments, the lithium-ion battery satisfies at least one of the following conditions:

[0072] A. The active material in the positive electrode sheet includes high nickel NCM, the chemical formula of which is LiNi x Co yMn z O 2 , 0.8≤x≤0.98, y≤0.2, z≤0.2, x+y+z=1;

[0073] It should be noted that the active material in the positive electrode sheet includes high-nickel NCM. NCM ternary materials combine the advantages of lithium cobalt oxide, lithium nickel oxide and lithium manganese oxide, and there is an obvious ternary synergistic effect. NCM ternary materials have higher energy density. The high-nickel positive electrode is matched with the silicon-oxygen negative electrode to produce a high-energy-density lithium-ion battery.

[0074] B. The surface density of the positive electrode is 45 mg / cm 2 -48mg / cm 2 ;

[0075] Optionally, the surface density of the positive electrode is 45 mg / cm 2 , 46mg / cm 2 , 47mg / cm 2 , 48mg / cm 2 or 45mg / cm 2 -48mg / cm 2 Any value in between.

[0076] C. The lithium-ion battery includes a 21700 lithium-ion battery;

[0077] It should be noted that the 21700 lithium-ion battery is a new generation of cylindrical steel-shell battery cells. Its main advantage is that it has higher space utilization, energy density and larger capacity than the traditional 18650 cylindrical lithium-ion battery. This feature allows the battery pack using 21700 batteries to reduce the number of cells under the same conditions, thereby improving the reliability of the overall system, reducing costs, and reducing the size of the battery pack, which can be adaptable and flexible in different fields.

[0078] D. The diaphragm includes one or more of a PP diaphragm, a PE diaphragm, and a ceramic-coated diaphragm.

[0079] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0080] Example 1

[0081] In a first aspect, the present embodiment provides a negative electrode active material, including graphite, silicon oxide and MnPS 3, silicon and oxygen account for 17% of the total mass of the negative electrode active material, MnPS 3 It accounts for 3% of the total mass of the negative electrode active material, and the rest is graphite.

[0082] The second aspect of this embodiment provides a negative electrode slurry, whose raw materials, calculated on a total mass basis, include 50% of the above-mentioned negative electrode active material, 13% of a conductive agent, 2% of a binder and 35% of water; the conductive agent includes conductive graphite and carbon nanotubes; and the binder includes PAA-CMC.

[0083] The preparation method of the negative electrode slurry is as follows: a binder and water are added into a double planetary mixer to prepare a glue solution, and a conductive agent and an active material are poured into the mixer for dry mixing; the prepared glue solution is added into the mixer three times to mix with the dry mixed material, and vacuum stirred for one hour until the slurry is evenly dispersed;

[0084] A third aspect of this embodiment provides a negative electrode sheet, the raw materials of which include the negative electrode slurry mentioned above.

[0085] A fourth aspect of the present embodiment provides a method for preparing a negative electrode sheet, comprising:

[0086] The negative electrode slurry was adjusted to a viscosity of 2100 mPa.s, and then coated on an 8 μm copper foil after vacuum sieving through a 100-mesh sieve. The slurry was then baked, rolled, and sheeted to obtain a surface density of 16 mg / cm 2 The negative electrode.

[0087] The fifth aspect of this embodiment provides a lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and a PP+ceramic coated separator; wherein the active material of the positive electrode sheet is a layered high-nickel NCM, and the chemical formula of the high-nickel NCM is LiNi x Co y Mn z O 2 , 0.8≤x≤0.98, y≤0.2, z≤0.2, x+y+z=1, the positive electrode active material, acetylene black, carbon nanotubes, a binder and a solvent are mixed to prepare a positive electrode slurry, the viscosity of the positive electrode slurry is adjusted to 2500mPa.s, the positive electrode slurry is coated on a 12μm aluminum foil, and baking, rolling and sheeting are performed in sequence to obtain a surface density of 47mg / cm 2 The positive electrode;

[0088] The prepared positive and negative electrode sheets and separators are wound, assembled, injected with liquid, and sealed to obtain a 21700 cylindrical lithium-ion battery.

[0089] Example 2

[0090] In a first aspect, the present embodiment provides a negative electrode active material, including graphite, silicon oxide and MnPS 3, silicon and oxygen account for 15% of the total mass of the negative electrode active material, MnPS 3 It accounts for 5% of the total mass of the negative electrode active material, and the rest is graphite.

[0091] The second aspect of this embodiment provides a negative electrode slurry, whose raw materials, calculated on a total mass basis, include 50% of the above-mentioned negative electrode active material, 13% of a conductive agent, 2% of a binder and 35% of water; the conductive agent includes conductive graphite and carbon nanotubes; and the binder includes PAA-CMC.

[0092] A third aspect of this embodiment provides a negative electrode sheet, the raw materials of which include the negative electrode slurry mentioned above.

[0093] A fourth aspect of the present embodiment provides a method for preparing a negative electrode sheet, comprising:

[0094] The negative electrode slurry was adjusted to a viscosity of 2100 mPa.s, coated on an 8 μm copper foil, and then baked, rolled, and sheeted to obtain a surface density of 16 mg / cm 2 The negative electrode.

[0095] The fifth aspect of this embodiment provides a lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and a PP+ceramic coated separator; wherein the active material of the positive electrode sheet is a layered high-nickel NCM, and the chemical formula of the high-nickel NCM is LiNi x Co y Mn z O 2 , 0.8≤x≤0.98, y≤0.2, z≤0.2, x+y+z=1, the positive electrode active material, acetylene black, carbon nanotubes, a binder and a solvent are mixed to prepare a positive electrode slurry, the viscosity of the positive electrode slurry is adjusted to 2500mPa.s, the positive electrode slurry is coated on a 12μm aluminum foil, and baking, rolling and sheeting are performed in sequence to obtain a surface density of 47mg / cm 2 The positive electrode;

[0096] The prepared positive and negative electrode sheets and separators are wound, assembled, injected with liquid, and sealed to obtain a 21700 cylindrical lithium-ion battery.

[0097] Example 3

[0098] In a first aspect, the present embodiment provides a negative electrode active material, including graphite, silicon oxide and MnPS 3 , silicon and oxygen account for 12% of the total mass of the negative electrode active material, MnPS 3 It accounts for 8% of the total mass of the negative electrode active material, and the rest is graphite.

[0099] The second aspect of this embodiment provides a negative electrode slurry, whose raw materials, calculated on a total mass basis, include 50% of the above-mentioned negative electrode active material, 13% of a conductive agent, 2% of a binder and 35% of water; the conductive agent includes conductive graphite and carbon nanotubes; and the binder includes PAA-CMC.

[0100] A third aspect of this embodiment provides a negative electrode sheet, the raw materials of which include the negative electrode slurry mentioned above.

[0101] A fourth aspect of the present embodiment provides a method for preparing a negative electrode sheet, comprising:

[0102] The negative electrode slurry was adjusted to a viscosity of 2100 mPa.s, coated on an 8 μm copper foil, and then baked, rolled, and sheeted to obtain a surface density of 16 mg / cm 2 The negative electrode.

[0103] The fifth aspect of this embodiment provides a lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and a PP+ceramic coated separator; wherein the active material of the positive electrode sheet is a layered high-nickel NCM, and the chemical formula of the high-nickel NCM is LiNi x Co y Mn z O 2 , 0.8≤x≤0.98, y≤0.2, z≤0.2, x+y+z=1, the positive electrode active material, acetylene black, carbon nanotubes, a binder and a solvent are mixed to prepare a positive electrode slurry, the viscosity of the positive electrode slurry is adjusted to 2500mPa.s, the positive electrode slurry is coated on a 12μm aluminum foil, and baking, rolling and sheeting are performed in sequence to obtain a surface density of 47mg / cm 2 The positive electrode;

[0104] The prepared positive and negative electrode sheets and separators are wound, assembled, injected with liquid, and sealed to obtain a 21700 cylindrical lithium-ion battery.

[0105] Example 4

[0106] In a first aspect, the present embodiment provides a negative electrode active material, including graphite, silicon oxide and MnPS 3 , silicon and oxygen account for 17% of the total mass of the negative electrode active material, MnPS 3 It accounts for 3% of the total mass of the negative electrode active material, and the rest is graphite.

[0107] The second aspect of this embodiment provides a negative electrode slurry, whose raw materials, calculated on a total mass basis, include 50% of the above-mentioned negative electrode active material, 13% of a conductive agent, 2% of a binder and 35% of water; the conductive agent includes conductive graphite and carbon nanotubes; and the binder is PAA.

[0108] A third aspect of this embodiment provides a negative electrode sheet, the raw materials of which include the negative electrode slurry mentioned above.

[0109] A fourth aspect of the present embodiment provides a method for preparing a negative electrode sheet, comprising:

[0110] The negative electrode slurry was adjusted to a viscosity of 2100 mPa.s, coated on an 8 μm copper foil, and then baked, rolled, and sheeted to obtain a surface density of 16 mg / cm 2 The negative electrode.

[0111] The fifth aspect of this embodiment provides a lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and a PP+ceramic coated separator; wherein the active material of the positive electrode sheet is a layered high-nickel NCM, and the chemical formula of the high-nickel NCM is LiNi x Co y Mn z O 2 , 0.8≤x≤0.98, y≤0.2, z≤0.2, x+y+z=1, the positive electrode active material, acetylene black, carbon nanotubes, a binder and a solvent are mixed to prepare a positive electrode slurry, the viscosity of the positive electrode slurry is adjusted to 2500mPa.s, the positive electrode slurry is coated on a 12μm aluminum foil, and baking, rolling and sheeting are performed in sequence to obtain a surface density of 47mg / cm 2 The positive electrode;

[0112] The prepared positive and negative electrode sheets and separators are wound, assembled, injected with liquid, and sealed to obtain a 21700 cylindrical lithium-ion battery.

[0113] Example 5

[0114] In a first aspect, the present embodiment provides a negative electrode active material, including graphite, silicon oxide and MnPS 3 , silicon and oxygen account for 17% of the total mass of the negative electrode active material, MnPS 3 It accounts for 3% of the total mass of the negative electrode active material, and the rest is graphite.

[0115] The second aspect of this embodiment provides a negative electrode slurry, whose raw materials, calculated on a total mass basis, include 50% of the above-mentioned negative electrode active material, 13% of a conductive agent, 2% of a binder and 35% of water; the conductive agent includes conductive graphite and carbon nanotubes; and the binder is CMC.

[0116] A third aspect of this embodiment provides a negative electrode sheet, the raw materials of which include the negative electrode slurry mentioned above.

[0117] A fourth aspect of the present embodiment provides a method for preparing a negative electrode sheet, comprising:

[0118] The negative electrode slurry was adjusted to a viscosity of 2100 mPa.s, coated on an 8 μm copper foil, and then baked, rolled, and sheeted to obtain a surface density of 16 mg / cm 2 The negative electrode.

[0119] The fifth aspect of this embodiment provides a lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and a PP+ceramic coated separator; wherein the active material of the positive electrode sheet is a layered high-nickel NCM, and the chemical formula of the high-nickel NCM is LiNi x Co y Mn z O 2 , 0.8≤x≤0.98, y≤0.2, z≤0.2, x+y+z=1, the positive electrode active material, acetylene black, carbon nanotubes, a binder and a solvent are mixed to prepare a positive electrode slurry, the viscosity of the positive electrode slurry is adjusted to 2500mPa.s, the positive electrode slurry is coated on a 12μm aluminum foil, and baking, rolling and sheeting are performed in sequence to obtain a surface density of 47mg / cm 2 The positive electrode;

[0120] The prepared positive and negative electrode sheets and separators are wound, assembled, injected with liquid, and sealed to obtain a 21700 cylindrical lithium-ion battery.

[0121] The 0.5C charging and 0.2C discharging capacity-voltage curves of the lithium ion batteries prepared in Example 1, Example 2 and Example 3 are as follows: Figure 1 shown.

[0122] The 0.5C charging and 1C discharging capacity-voltage curves of the lithium ion batteries prepared in Example 1, Example 2 and Example 3 are as follows: Figure 2 shown.

[0123] The capacity retention rates of the lithium ion batteries prepared in Example 1, Example 2 and Example 3 at 0.5C, 1C, 2C, 3C, 4C, 5C and 6C rates compared with 0.2C rate charging are as follows: Figure 3 shown.

[0124] The 25°C cycle capacity retention rates of the lithium ion batteries prepared in Example 1, Example 2 and Example 3 are as follows: Figure 4 shown.

[0125] Comparative Example 1

[0126] This comparative example provides a negative electrode active material, a negative electrode slurry, a negative electrode sheet and a preparation method thereof, and a lithium ion battery. The difference from Example 1 is that the negative electrode active material of this comparative example does not contain MnPS 3 , silicon oxide accounts for 17% of the total mass of the negative electrode active material, and the rest is graphite. Other conditions are consistent with Example 1.

[0127] Comparative Example 2

[0128] This comparative example provides a negative electrode active material, a negative electrode slurry, a negative electrode sheet and a preparation method thereof, and a lithium ion battery. The difference from Example 1 is that: MnPS 3 The total mass of the negative electrode active material is 10%, the total mass of the negative electrode active material is 17%, and the rest is graphite. Other conditions are the same as those in Example 1.

[0129] Comparative Example 3

[0130] This comparative example provides a negative electrode active material, a negative electrode slurry, a negative electrode sheet and a preparation method thereof, and a lithium ion battery. The difference from Example 1 is that: MnPS 3 The total mass of the negative electrode active material is 1%, the total mass of the negative electrode active material is 17%, and the rest is graphite. Other conditions are consistent with those in Example 1.

[0131] Comparative Example 4

[0132] This comparative example provides a negative electrode active material, a negative electrode slurry, a negative electrode sheet and a preparation method thereof, and a lithium ion battery. The difference from Example 1 is that this comparative example does not add silicon oxide compounds, MnPS 3 It accounts for 3% of the total mass of the negative electrode active material, and the rest is graphite. Other conditions are consistent with Example 1.

[0133] The lithium-ion batteries prepared in the above-mentioned embodiments and comparative examples were subjected to charging performance tests at different rates, and the specific test steps are shown in Table 1.

[0134] Table 1 Rate charging performance test steps

[0135]

[0136]

[0137]

[0138] The test results of charging performance at different rates according to the steps in Table 1 are shown in Table 2.

[0139] Table 2 Rate charging performance test data

[0140] sample 0.2C 0.5C 1C 2C 3C 4C 5C 6C Example 1 6100 5908 5831 5633 5349 5226 4895 4647 Example 2 5950 5934 5812 5762 5583 5525 5502 5476 Example 3 5680 5664 5612 5586 5557 5444 5504 5443 Example 4 6120 6028 5701 5360 4904 4762 4634 4383 Example 5 6100 6071 5876 5493 5086 4751 4549 4422 Comparative Example 1 6000 5800 5700 5230 4850 4450 4210 4080 Comparative Example 2 6080 5900 5850 5650 5300 5240 4900 4610 Comparative Example 3 6030 5910 5790 5360 4980 4790 4560 4210 Comparative Example 4 4900 4886 4876 4855 4861 4866 4861 4860

[0141] The lithium-ion batteries prepared in the above embodiments and comparative examples were subjected to capacity separation tests. First, they were charged to 4.2V at a current of 0.5C, then kept at a constant voltage of 4.2V to 0.05C, and then discharged at currents of 0.2C and 1C, respectively. The specific capacity separation test results are shown in Table 3.

[0142] Table 3 Capacity test

[0143]

[0144] The lithium-ion batteries prepared in the above examples and comparative examples were subjected to a 25° C. cycle test to explore their 1C cycle life. The test conditions are shown in Table 4.

[0145] Table 4 Cyclic test conditions

[0146]

[0147] The results of the 25°C cycle test performed according to the steps in Table 4 are shown in Table 5.

[0148] Table 5 Cyclic test results

[0149]

[0150] From the above test results, it can be seen that adding MnPS to the negative electrode active material 3 It is beneficial to improve the effects of short cycle life and poor rate performance caused by silicon-oxygen expansion. The use of PAA-CMC as a binder further enhances the pole piece strength and electrode conductivity.

[0151] During the charge and discharge process, the expansion of silicon oxide caused by lithium ion deintercalation will cause the active material to fall off, destroy the stability of the pole structure, and greatly reduce the service life of the lithium-ion battery. 3 It can effectively improve the negative effects caused by silicon-oxygen expansion; when MnPS 3 When the mass of MnPS accounts for 3%-8% of the total mass of the negative electrode active material, 3 The higher the content, the better the rate performance and cycle performance; mainly due to metal phosphorus trisulfide MnPS 3 It has a unique layered van der Waals structure, which is conducive to the rapid deintercalation of alkali metal ions. When storing lithium ions, the single-phase phosphorus heterogeneous structure is accompanied by irreversible breakage of PS bonds after the first charge and discharge cycle. The mixed phases formed in situ can be used as inert buffer matrices for each other, thereby buffering the aggregation and crushing of the electrodes caused by volume changes. When MnPS 3 When the mass of MnPS is less than 3% of the total mass of the negative electrode active material, it cannot effectively alleviate the expansion of silicon and oxygen during lithium insertion, resulting in cracking of the negative electrode sheet during the electrochemical reaction and a significant reduction in service life. 3 The gram capacity of MnPS and graphite is 370-380 mAh / g. 3 When the mass proportion of MnPS is higher than 8% of the total mass of the negative electrode active material, its advantage in improving the battery capacity is not significant; in addition, a high proportion of MnPS 3 This will make the dispersion of the slurry worse, causing the powder particles to easily agglomerate. This not only reduces the yield rate of the negative electrode sheet, but also increases the production cost; high proportion of MnPS 3The rate performance and cycle performance of the prepared lithium-ion battery have no obvious improvement.

[0152] The use of PAA-CMC as a binder has a longer cycle life than using PAA or CMC alone; PAA-CMC forms a three-dimensional cross-linked network through esterification reaction, increases stress nodes, has high mechanical strength and good electrochemical coupling effect, and enhances the electrode conductivity. PAA-CMC contains abundant carboxyl and hydroxyl groups, which may react with MnPS 3 Coupling and sustained activation of MnPS 3 , thereby reducing the reduction potential barrier and achieving high utilization of active materials. 3 The phosphorus in the MnPS generates strong interfacial interactions and is evenly distributed in the 3 The surface of the electrolyte is isolated from the active material and the electrolyte is directly contacted. It helps to form a thin solid electrolyte interface layer (SEI) and reduce the irreversible loss of active materials.

[0153] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0154] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A negative electrode active material, characterized in that: Including graphite, silicon oxide and MnPS3; The mass of the silicon oxide compound accounts for 12%-17% of the total mass of the negative electrode active material; The mass of the MnPS3 accounts for 3%-8% of the total mass of the negative electrode active material.

2. A negative electrode slurry, characterized in that: The raw materials thereof, calculated on the basis of total mass as 100%, include 48%-52% of the negative electrode active material according to claim 1, 10%-15% of a conductive agent, 2%-6% of a binder and 30%-35% of a solvent.

3. The negative electrode slurry according to claim 2, characterized in that: At least one of the following conditions is met: A. The conductive agent includes one or more of conductive graphite, carbon nanotubes, and graphene; B. The solvent includes water.

4. The negative electrode slurry according to claim 2 or 3, characterized in that: The binder includes sodium polyacrylate and / or sodium carboxymethyl cellulose.

5. A negative electrode sheet, characterized in that: The raw material includes the negative electrode slurry described in any one of claims 2 to 4.

6. A method for preparing a negative electrode sheet according to claim 5, characterized in that: include: slurry-adjusting the negative electrode slurry to obtain slurry-adjusted slurry; The slurry after slurry adjustment is coated on a current collector to obtain the negative electrode sheet.

7. The method for preparing a negative electrode sheet according to claim 6, characterized in that: The viscosity of the slurry after slurry adjustment is 1900mPa.s-2200mPa.s.

8. The method for preparing a negative electrode sheet according to claim 6, characterized in that: The surface density of the negative electrode sheet is 15 mg / cm 2 -18mg / cm 2 .

9. A lithium ion battery, characterized in that: The negative electrode sheet, positive electrode sheet and separator are prepared by the negative electrode sheet according to claim 5 or the method for preparing the negative electrode sheet according to any one of claims 6 to 8.

10. The lithium ion battery according to claim 9, characterized in that: At least one of the following conditions is met: A. The active material in the positive electrode sheet includes high nickel NCM, the chemical formula of which is LiNi x Co y Mn z O2, 0.8≤x≤0.98, y≤0.2, z≤0.2, x+y+z=1; B. The surface density of the positive electrode is 45 mg / cm 2 -48mg / cm 2 ; C. The lithium-ion battery includes a 21700 lithium-ion battery; D. The diaphragm includes one or more of a PP diaphragm, a PE diaphragm, and a ceramic-coated diaphragm.